Shrub encroachment is not always land degradation: Insights from ground‐dwelling beetle species niches along a shrub cover gradient in a semi‐arid Namibian savanna. (8th November 2018) - Hering, Robert; Hauptfleisch, Morgan; Geißler, Katja; Marquart, Arnim; Schoenen, Maria; Blaum, Niels
Abstract: Shrub encroachment in semi‐arid savannas is induced by interacting effects of climate, fire suppression, and unsustainable livestock farming; it carries a severe risk of land degradation and strongly influences natural communities that provide key ecosystem functions. However, species‐specific effects of shrub cover on many animal groups that act as indicators of degradation remain largely unknown. We analysed the consequences of shrub encroachment for ground‐dwelling beetles in a semi‐arid Namibian savanna rangeland, where beetles and vegetation were recorded along a shrub cover gradient (<1% to >30%). Focusing on species niche breadths and optima, we identified two crucial shrub cover thresholds (2.9% and 10.0%), corresponding to major changes in the beetle communities with implications for savanna ecosystem functioning. Niche optima of most species were between the first and second thresholds; beyond the second threshold, saprophagous, coprophagous, and rare predatory beetles declined in numbers and diversity. This is problematic because beetles provide important ecosystem functions, such as decomposition and nutrient cycling. However, we also found that certain species were adapted to high shrub cover, thus providing examples of niche differentiation. Despite the predominantly negative effects of heavy shrub encroachment on beetle communities, shrubs in their early life stages apparently provide essential structures, which enhance habitat quality for ground‐dwelling beetles. Our results demonstrate that shrub encroachment can have mixed effects on ground‐dwelling beetle communities and hence on savanna ecosystem functioning. We, therefore, conclude that rangeland management and restoration should consider the complex trade‐offs between species‐specific effects and the level of encroachment for sustainable land use.